2019
DOI: 10.15376/biores.14.3.5788-5806
|View full text |Cite
|
Sign up to set email alerts
|

Wheat bran as substrate for enzyme production and its application in the bio-deinking of mixed office waste (MOW) paper

Abstract: Judicial utilization of various low-cost agro-industrial wastes and optimization of various process parameters can reduce production costs of enzymes. Wheat bran was found to be the best carbon source among various agro-industrial wastes explored for Penicillium citrinum NCIM-1398. Additionally, ammonium sulphate was found as the optimum nitrogen source at moisture content 70%, pH 5.5, and temperature 30 °C for enzyme production. The maximal enzyme activities of endo β-1,4-glucanase, xylanase, FPase, and amyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Therefore, it has been recognised that using agricultural waste as the sole carbon source for xylanase synthesis could be a good solution. Although wheat bran is considered a waste, there is strong evidence that the bran is recognised as a suitable substrate for xylanase production because of its hemicellulosic nature (presence of nonstarch polysaccharides, 41 to 60 %), favourable degradability and the presence of some nutrients ( 24 , 25 ). Furthermore, the biochemical composition shows that after hydrolysis of wheat bran, significant amounts on dry mass basis of soluble sugars such as glucose (42.5 %), xylose (15.4 %), arabinose (3.1 %) and galactose (2.7 %) are produced, which are necessary to initiate the growth of microorganism and promote their further growth ( 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it has been recognised that using agricultural waste as the sole carbon source for xylanase synthesis could be a good solution. Although wheat bran is considered a waste, there is strong evidence that the bran is recognised as a suitable substrate for xylanase production because of its hemicellulosic nature (presence of nonstarch polysaccharides, 41 to 60 %), favourable degradability and the presence of some nutrients ( 24 , 25 ). Furthermore, the biochemical composition shows that after hydrolysis of wheat bran, significant amounts on dry mass basis of soluble sugars such as glucose (42.5 %), xylose (15.4 %), arabinose (3.1 %) and galactose (2.7 %) are produced, which are necessary to initiate the growth of microorganism and promote their further growth ( 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…Kopania et al (2008) reported a 5% increase in pulp brightness during the peroxidase bleaching of MOW paper with MgSO4 and EDTA. Brogdon et al (1998) also reported enhanced brightness at high-temperature peroxide bleaching of MOW using formulated bleach stabilizers.…”
Section: Table 1 Properties Of Mow Pulp After Pulping and Biodeinkingmentioning
confidence: 90%
“…MOW paper also shows poor bleachability with the commonly used chemical bleaching agents, including chlorine dioxide, oxygen, hydrogen peroxide, and sodium dithionite (Knutson et al 2005). To overcome the poor bleachability of MOW pulp by chemical agents, a wide number of enzymes, including cellulase (Tiwari et al 2018), xylanase (Kumar et al 2017), laccase (Riva 2006;Singh and Arya 2019), and peroxidase (Archibald 1992), have been studied (Biswas et al 2019b). The enzyme application in pulp and paper industry are limited due to their high cost, and it is hard to maintain their stability during the industrial process (Kumar et al 2018b(Kumar et al ,c, 2019aLin et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation